Influency of granulometric over adaptation and support of meiofauna on sandy beach at Olinda's Isthmus-PE - BEZERRA, T. N. C. (Associação Brasileira de Ciência Ecológica e Conservação (ABECO), 2010)
The meiofauna from Isthmus of Olinda (Lat. 8° 2' 24" S; Long. 34° 51' 48"W) was collected from November/1988 to October/1989, in seven transects, with distance on 300m between each other, and stations at supratidal, intertidal and subtidal level. The granulometric analysis showed a sediment with predominance of medium sands. Accordind to effective diameter, it was evident that inside medium sand class, the variance of grain size demanded a subdivision to verify the effect of granulometry in animais distribution. So, the fraction medium sand was subdivided on: higer, intermediate and smaller. With XÂ² test was showed that Nematoda was indifferent to this granulometric variance, while Copepoda Harpacticoida and Ostracoda suffered influence by granulometry probably because they seem more adapted to swimming.